Effect of Material on The Fracture Resistance of Three-Unit Endocrown Retained Bridge on Endodontically Treated Abutments - Hend Elkawash; Salima Aoun; Mohamed Algundi; Ehab Dauki (Khalij-Libya Journal of Dental and Medical Research, 2025)
This study aimed to evaluate the effect of material selection on the fracture resistance of a three-unit endocrown-retained bridge placed on endodontically treated abutments. Two restorative materials were investigated: lithium disilicate (IPS e.max Press, Ivoclar Vivadent) and high-performance polymer (BioHPP, Bredent GmbH). A total of 14 samples were fabricated using standardized preparation techniques, with each material group comprising seven samples. Endocrown retainers were designed using CAD/CAM technology and cemented with adhesive resin cement (3M RelyX™ Ultimate). The samples underwent thermomechanical aging using a chewing simulator, followed by static fracture testing in a universal testing machine to assess their load-bearing capacity. Statistical analysis revealed that the IPS e.max Press group exhibited higher fracture resistance (1505.8 ± 57.79 N) than the BioHPP group (1352.2 ± 113.54 N), with a statistically significant difference (p = 0.0026). Despite this, both materials demonstrated fracture resistance values exceeding the functional occlusal forces encountered in clinical settings. Endocrown-retained bridges fabricated from IPS e.max Press and BioHPP exhibit clinically acceptable fracture resistance. However, IPS e.max Press demonstrated superior mechanical properties, making it a more reliable choice for endocrown-retained restorations. BioHPP restorations, while slightly less resistant, offer advantages in terms of biocompatibility and wear resistance. Further research is recommended to explore long-term clinical performance. هدفت هذه الدراسة إلى تقييم تأثير اختيار المواد على مقاومة الكسر لجسر مكون من ثلاث وحدات مثبت بالتاج الداخلي موضوع على دعامات معالجة لبيًا. تم التحقيق في مادتين ترميميتين: ثنائي سيليكات الليثيوم والبوليمر عالي الأداء. تم تصنيع ما مجموعه 14 عينة باستخدام تقنيات تحضير موحدة، حيث تتكون كل مجموعة مواد من سبع عينات. تم تصميم مثبتات التاج الداخلي باستخدام تقنية CAD / CAM وتم تثبيتها بإسمنت راتنجي لاصق. خضعت العينات للشيخوخة الحرارية الميكانيكية باستخدام محاكي المضغ، تلا ذلك اختبار الكسر الثابت في آلة اختبار عالمية لتقييم قدرتها على تحمل الحمل. كشف التحليل الإحصائي أن مجموعة ثنائي سيليكات الليثيوم أظهرت مقاومة أعلى للكسر (1505.8 ± 57.79 نيوتن) من مجموعة البوليمر عالي الأداء (1352.2 ± 113.54 نيوتن)، مع وجود فرق كبير إحصائيًا (ص = 0.0026). وعلى الرغم من ذلك، أظهرت كلتا المادتين قيم مقاومة للكسر تتجاوز قوى الإطباق الوظيفية التي واجهتها في الإعدادات السريرية. تُظهر الجسور المدعومة بالتاج الداخلي المصنوعة من ثنائي سيليكات الليثيوم والبوليمر عالي الأداء مقاومة مقبولة سريريًا للكسر. ومع ذلك، أظهرت ثنائي سيليكات الليثيوم خصائص ميكانيكية متفوقة، مما يجعلها خيارًا أكثر موثوقية للحشوات المدعومة بالتاج الداخلي. توفر الحشوات المدعومة بالتاج الداخلي، على الرغم من كونها أقل مقاومة قليلاً، مزايا من حيث التوافق الحيوي ومقاومة التآكل. يوصى بإجراء مزيد من البحث لاستكشاف الأداء السريري طويل الأمد.